Risk markers for physical intimate partner violence victimization: A meta-analysis. (January 2019) - Spencer, Chelsea M.; Stith, Sandra M.; Cafferky, Bryan
Abstract: This meta-analysis provides a comprehensive overview of risk markers for intimate partner violence (IPV) victimization. Data from 391 studies, yielding 1731 effect sizes, were analyzed. Using Dutton's (1995) nested ecological theory, we categorized risk markers into the exosystem, microsystem, and ontogenetic levels. We examined 50 risk markers for IPV victimization for women, and 28 risk markers for IPV victimization for men. Using a random-effects approach, the overall strength of each risk marker for men and women was calculated to find out which risk markers were most strongly correlated with IPV victimization for both men and women. Next, gender was used as a moderator on 28 risk markers to test if there was a significant difference in the strength of risk markers between men and women. We found that the strongest risk markers for IPV victimization for both men and women were risk markers located in the microsystem, and specifically risk markers associated with previous relationship violence. We also found that the strength of 5 out of 28 risk markers for IPV victimization significantly differed between men and women (alcohol use, child abuse in family of origin, depression, older age, sexual IPV victimization). Implications for future research and for clinicians are discussed. Highlights: The strongest risk markers for intimate partner violence (IPV) victimization were associated with previous relationship violence. Risk markers for IPV victimization were more similar between men and women than they were distinctly different. Five out of 28 risk markers did significantly differ in strength between men and women, which included alcohol use, child abuse in family of origin, depression, older age, and sexual IPV victimization.